2022
DOI: 10.3390/su14148700
|View full text |Cite
|
Sign up to set email alerts
|

Foundation Settlement Response of Existing High-Speed Railway Bridge Induced by Construction of Undercrossing Roads

Abstract: The construction of undercrossing roads often has an adverse effect on the upper existing railway line, and can cause an uneven subsidence of the crossed section. In response to the influence of new road construction on the existing high-speed railway bridge, a highway passing under an existing high-speed railway bridge was taken as the research object. Based on the FLAC3D finite difference software, a computational model of new roads undercrossing a high-speed railway bridge was established to analyze the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The longitudinal and transverse reinforcements in the pier are simulated using the Hughes-Liu beam element with one integral point. The concrete is assumed to be fully bonded to the reinforcements, implemented by the keyword *CONSTRAINED_LAGRANGE_IN_SOLID [5,17]. The effect of the superstructure is considered by using the keyword *LOAD_BODY_Z.…”
Section: Fe Model Of Bridge and Rockfallmentioning
confidence: 99%
“…The longitudinal and transverse reinforcements in the pier are simulated using the Hughes-Liu beam element with one integral point. The concrete is assumed to be fully bonded to the reinforcements, implemented by the keyword *CONSTRAINED_LAGRANGE_IN_SOLID [5,17]. The effect of the superstructure is considered by using the keyword *LOAD_BODY_Z.…”
Section: Fe Model Of Bridge and Rockfallmentioning
confidence: 99%
“…Liu, J. et al [5] studied the causes of a settlement disease of the double-pillar pier foundation of a newly built highway bridge and found that an insufficient bearing capacity and pile body defects caused an uneven settlement of the pile foundation. Wang, Y. et al [6] established the underpass highway model of a high-speed railway bridge by the finite element analysis method and analyzed the settlement between the highway and the bridge. Zhang et al [7] conducted a numerical simulation study and believed that the shield tunneling technology used in tunnel construction under existing bridges had little influence on the settlement of the existing bridges.…”
Section: Introductionmentioning
confidence: 99%